Effect of Charlson Comorbidity Index and Treatment Strategy on Survival of Elderly Patients After Endoscopic Submucosal Dissection for Gastric Adenocarcinoma: A Multicenter Retrospective Study - Cao, Wenzhe; Liu, Shaohua; Wang, Shasha; Wang, Shengshu; Song, Yang; He, Yao (Frontiers in Public Health, 2022)
Background: The optimal treatment strategy after non-curative endoscopic submucosal dissection (ESD) remains unclear in elderly patients with early gastric adenocarcinoma (EGAC). The aim of the study was to explore the validity of additional treatments after non-curative ESD and survival predictors in elderly patients (≥60 years) with EGAC population. Methods: A total of 639 elderly patients (≥60 years) treated with ESD for EGAC from 2006 to 2018 were retrospectively reviewed. Patients were stratified into three groups on the basis of the lymph node metastasis risk, histological findings (high-risk factors: positive lymphovascular invasion, submucosal invasion, and positive/indeterminate vertical margin), and the post-ESD treatment strategy: group A (482 patients; low risk), group B (121 patients; high risk, without additional treatment), and group C (36 patients; high risk, with additional treatment). The 5- and 8-year overall survival and disease-specific survival, and prognostic factors for post-ESD survival were investigated. Results: At a median follow-up of 38, 40, and 49 months, respectively, there was 4 gastric adenocarcinoma related death in group A, 3 in group B, and 3 in group C, whereas 20, 5, and 3 patients in groups A, B, and C died of other diseases. The groups differed significantly in overall survival (94.3%; 86.4%; 81.2%, p= 0.110), although not in disease-specific survival (98.4%; 92.7%; 92.4%, p= 0.016). On multivariate analysis, Charlson Comorbidity Index (CCI)≥2 was the independent risk factor for post-ESD death (hazard ratio 2.39; 95% confidence interval 1.20–4.77; p=0.014). Conclusions: The strategy of ESD with no subsequent additional treatment for EGAC may be a suitable option for elderly patients in high risk, especially for CCI≥2.